Emotion Recognition and Differentiation in Cannabis Abstainers Over Time: Assessing the Role of Mental Health Problems and Cannabis Withdrawal - Kumari, Aradhana; Shukla, Meenakshi; Singh, Rakesh Kumar (European Journal of Mental Health, 2024)
Introduction: Cannabis is the second most widely-used substance in India, after alcohol. Several researches show how cannabis use can impair emotion recognition capacity, but relatively few researchers have explored this among cannabis abstainers. Aims: The present study’s authors aimed at assessing emotion recognition, emotion differentiation, self-reported anxiety, depression, stress, withdrawal intensity and impact in a sample of men who abstain from cannabis. Methods: Heavy cannabis users (N = 70 males) were assessed via questionnaires regarding their cannabis use frequency, their age at onset of usage, anxiety, depression, and stress levels as well as their performance on computerised tasks of emotion recognition and discrimination within 24 hours of their admission (T0), then after 15 days of abstinence (T1), and finally after 30 days of abstinence (T2). At T1 and T2, they were also assessed for withdrawal intensity and the impact of withdrawal on daily activities. Results: Findings revealed that, with abstinence, successive improvement in emotion recognition and emotion differentiation developed, even after accounting for declines in psychological distress from T0 to T1. However, from T1 to T2, further declines in psychological distress and withdrawal impact mainly accounted for this improvement. Happiness was the best recognised and well-differentiated emotion while the poorest discrimination was observed for anger. Conclusions: This study’s findings corroborate and significantly add to the limited existing literature, demonstrating improved emotion recognition and differentiation due to initial cannabis abstinence, but later this improvement proceeds with a decline in distress and withdrawal impact.